Comparison of Immune Responses Elicited by SARS-CoV-2 mRNA and Recombinant Protein Vaccine Candidates - Wu, Yixin; Zhang, Huicong; Meng, Liuxian; Li, Fusheng; Yu, Changyuan (Frontiers in Immunology, 2022)
After the outbreak of COVID-19, billions of multiple types of vaccines have been administrated, including recombinant protein vaccines and mRNA vaccines. Although both types of SARS-CoV-2 vaccine can protect people from viral infection, their differences in humoral and cellular immune responses are still not clearly understood. In this study, we made a head-to-head comparison between an mRNA vaccine candidate and a recombinant protein vaccine we developed previously. Results demonstrated that both vaccine candidates could elicit high specific binding and neutralizing antibody titers in BALB/c mice, but with bias towards different IgG subtypes. Besides, the mRNA vaccine candidate induces higher cellular immune responses than the recombinant protein vaccine. As we know, this is the first reported study to directly compare the immune responses of both arms between SARS-CoV-2 mRNA and recombinant vaccines.